Development of an automated system for controlling the temperature regime of baking bakery products using a fuzzy controller - Razzhyvin, O. V.; Liuta, A.; Simkin, O. I.; Zaliatov, A.; Разживін, О. В.; Люта, А.; Сімкін, О. І.; Залятов, А. (Дніпровський національний університет імені Олеся Гончара, 2024)
The purpose of the work is to improve the main indicator of the economic efficiency of the production of bakery products - the saving of electricity for heating inside the baking chamber. Design / Method / Approach. Achieving the goal in the work is carried out by eliminating the possibility of supplying excess heat from heaters by modernizing the automated baking temperature control system. A mathematical model of the automated control system for the temperature mode of baking in a tunnel-type bakery oven was developed using the methods of designing intelligent control systems. The technological process is controlled using a fuzzy controller. Findings. Control of the parameters of the internal environment in the cameras was achieved by automated control of actuators. Conducting the technological process from start to finish without operator intervention provides the possibility of remote change of baking modes without stopping the process. Control algorithms for the technological process of baking bakery products have been developed, which exclude incorrect operations. Theoretical Implications. According to the results of theoretical research on the mathematical model of the fuzzy control system of the technological process of the production of bakery products, surfaces of the fuzzy control of the technological process of baking by capacity and humidity were obtained. Practical Implications. The proposed automated system for controlling the temperature mode of baking bakery products, the operation of the heater and humidifier is adjusted by a fuzzy controller. Originality / Value. The simulation results show that the use of fuzzy controllers in automatic control systems allows controlling temperature and humidity at the stages of bread baking. Research Limitations / Future Research. The fuzzy controller proposed in the article can control the power of the heater in three positions, the humidity level in three levels, and the baking stage in 3 stages. Paper Type. Practitioner Paper.
Розробка автоматизованої системи управління температурним режимом випікання хлібобулочних виробів із використанням нечіткого контролера
Keywords: automated control system; baking temperature control; fuzzy controller